Nilai dan Kualitas Emas Dinar pada Komunitas Magnet Rezeki Banda Aceh dalam Tinjauan Syarat Objek Jual Beli Menurut Fiqh Muamalah - Nida Ufairah; Bukhari Ali; Nahara Eriyanti (Jurnal Investasi Islam, 2024)
Dinar Khoirur Roziqiin is a Magnet Rezeki community product. Although the quality standard of this dinar is in accordance with LBMA regulations, the existence of value and quality is still a concern among people outside Magnet Rezeki because people still doubt the quality standards. Therefore, empirical evidence is needed so that the standard and quality can be recognized by all circles and in accordance with the provisions of Fiqh Muamalah. Based on these problems, this research was conducted with the aim of examining the value and quality of dinars among Magnet Rezeki in reviewing the terms of the object of sale and purchase according to Fiqh Muamalah. This research uses qualitative methods with descriptive analysis type of research. The results of this study indicate that the value and quality of dinars Khoirur Roziqiin's are in accordance with the provisions of the terms of the object of sale and purchase in Fiqh Muamalah. The parties involved in production, certification and sale have ensured that the value and quality of this dinar is maintained. Therefore, the results of this study are expected to provide empirical information to all groups regarding the value and quality of this dinar. As a result, it’s expected to increase the trust and interest of Magnet Rezeki members and the public to invest in dinar Khoirur Roziqiin. The author suggests that the dinar Khoirur Roziqiin company carefully ensure the transparency of the value and quality of dinar. In addition, the company must conduct vigorous education to the wider community about the benefits of dinar investment.